Gender-based violence care in Mauritania: Experience and caseload of six specialized hospital units (2018-2023). - Clairanne Bost; Mouhamedou Diagana; Houssein Lebkem (Public Library of Science (PLoS), 2024)
Since 2017, six specialized care units, the USPEC (Unités Spéciales de Prise en Charge) have been implemented in Mauritanian hospitals with the support of the international organization Médicos del Mundo. They provide healthcare and comprehensive assistance to victims of gender-based violence (GBV), such as sexual violence (SV), intimate-partner violence (IPV), female genital mutilation (FGM), adolescent pregnancy and child marriage. In this retrospective, observational study, we investigated the caseload of the six USPEC countrywide between January 1st, 2018, and June 30th, 2023. We analyzed consultation data, victims' sociodemographic characteristics, types of violence they were subjected to, specific patterns-location, relationship with the perpetrator, reoccurrence-, and medical care they received. 3550 cases were attended to, with a threefold increase in the mean number of monthly cases between 2018 and 2023. Women and girls accounted for 95.1% of victims; 78.7% were under 18 years old and 21.9% were under 12. All male victims (n = 172) were children. SV represented 79.8% of the caseload, early marriage/pregnancy 10.4%, IPV 7%, and FGM 0.7%. 80% of perpetrators were known to the victims, and the acts of violence had taken place in the victims´ own home for 60%. The proportion of cases received within 72 hours increased noticeably within the first two years before stabilizing at an average 81.3%. 7.21% of patients received local or surgical treatment and 1.8% were hospitalized. After SV, 996 received emergency contraception while 627, who sought care with delay, were already pregnant. Our findings suggest that the USPEC model responds to both victims' and the health system's needs to address GBV. Prevention, declaration and follow-up of pregnancy as a result of SV in young girls, likely constituted a major motivation for healthcare-seeking, yet more research is needed to document bottlenecks faced by GBV victims to access such services.